A Passivity Approach to the Stabilization of Free-Radical Polymerization Reactor - Nguyen, T. Sang; Hoang, N. Ha; Hussain, M. A. (ASEAN Journal of Chemical Engineering, 2017)
This work proposes a tracking error passivity-based multivariable control via feedback passivation for a class of free-radical polymerization systems in a continuously stirred tank reactor (CSTR). Firstly, this system dynamics with high nonlinearity is passivized by input coordinate transformations, the resulting passive system is then rewritten into a canonical form strongly related to the so-called Port Control Hamiltonian structure. Actually, this representation allows to show the physical meanings of system dynamics such as dissipative, non-dissipative terms and supply rate. From this, a feedback controller based on tracking error is designed for the globally exponential stabilization at an arbitrarily chosen reference trajectory passing the desired equilibrium point. The theoretical developments are then illustrated for polystyrene polymerization system in the CSTR. The numerical simulations show that the trajectories of styrene polymerization system considered as an illustrative example of FRP system converges globally exponentially to the imposed trajectories.